Brief communication:preliminary investigation on the relationship of the nominate C. brachyotis with the small-sized and large-sizedC . brachyotis using clustering analysis - Jayaraj V.K; M.T. Abdullah (2006)
Previous studies have shown that ecological habitats are the driving force that lead to genetic and morphological divergence in Cynopterus brachyotis populations in Malaysia. In this study, we have shown that the type specimen is clustered with a large-sized C. brachyotis which is normally found is open habitats.Futher clustering analysis is necessary to include the five species of Cynopterus in order to verify if there is a new species within the C.brachyotis populations